2012
DOI: 10.1538/expanim.61.417
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an Experimental Mouse Model of Trauma-Hemorrhagic Shock

Abstract: This study established an experimental mouse model of trauma-hemorrhagic shock (THS). THS-induced mice (C57BL/6J, n=33) were subjected to femoral fracture, ischemia for 90 min, and resuscitation for 15 min. The sham-operated mice (C57BL/6J, n=33) underwent the same anesthetic and surgical procedures, but neither trauma-hemorrhage nor fluid resuscitation were performed. Mean arterial pressure (MAP) and microvascular tissue perfusion over the small intestine, liver, and left kidney were longitudinally measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…In the past, numerous reports describing animal models for the study of multiple trauma, incl. fracture and hemorrhagic shock have been published . These studies demonstrated dysfunction of posttraumatic immune response, changes in IL‐6 expression following multiple trauma and hemorrhagic shock or tested the efficacy of rejuvenation of the immune system by bone marrow transplantation on fracture repair .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the past, numerous reports describing animal models for the study of multiple trauma, incl. fracture and hemorrhagic shock have been published . These studies demonstrated dysfunction of posttraumatic immune response, changes in IL‐6 expression following multiple trauma and hemorrhagic shock or tested the efficacy of rejuvenation of the immune system by bone marrow transplantation on fracture repair .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors publish hemorrhagic shock models in combination with sepsis or isolated limb injury . These studies using different models and fracture methods were restricted either to rats and mice that did either not survive the acute period (more than 72 h) or did not allow long‐term analysis of fracture healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under normotensive conditions circulating leukocytes flow freely through the sinusoids of the liver, evoking no interactions with the vascular endothelium. Circulatory disturbance results in sinusoidal congestion with increased leukocyte activation (21,22) as well as increased leukocyte endothelial interactions (7).…”
Section: Stages and Consequences Of Hemorrhagic Shockmentioning
confidence: 99%